EFFECTS OF AQUEOUS EXTRACT OF GLYCYRRHIZA GLABRA LINN. AND DIOSMETIN ON MODULATION OF SPATIAL MEMORY THROUGH ACETYLCHOLINESTERASE AND BRAIN-DERIVED NEUROTROPHIC FACTOR IN ETHANOL-INDUCED COGNITIVE IMPAIRMENT MODEL RATS - A, Sasikumar; S, Suba Malani; S, Manikandan; C, Ramaswamy; S, Senthilkumar (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research was to evaluate the cognitive impairment due to excessive consumption of alcohol and memory enhancement action of Glycyrrhiza glabra Linn. (AEGGL) and diosmetin (Dm). Methods: In this study, 36 adult male Wistar rats were divided into the six groups (n=6) and eight-arm radial maze, narrow beam test, and open field behavior parameters were assessed on day 1, 10, and 21. After the 21 days of experiment, animals were sacrificed, and blood samples were collected for serum acetylcholinesterase (AChE) and brain-derived neurotrophic factor (BDNF) estimation. We have also analyzed the morphology of CA3 region of the hippocampus. Results: The results of this study suggested that AEGGL and Dm treatment could be the potential drugs for ethanol-induced cognitive impairment. Conclusion: Ethanol-induced cognitive impairment was recovered by AEGGL and Dm treatment, we suggested that this might be due to anticholinesterase activity and increased synthesis of BDNF levels in the brain. Further, researches are warranted to understand the exact mechanism of action of drugs.